Face-to-face communication over the Internet emotions in a web of culture, language, and technology - Kappas, Arvid; Krämer, Nicole C. (Cambridge, [England] Cambridge University Press, 2011)
"Social platforms such as MySpace, Facebook and Twitter have rekindled the initial excitement of cyberspace. Text based computer-mediated communication has been enriched with face-to-face communication such as Skype, as users move from desk tops to laptops with integrated cameras and related hardware. Age, gender and culture barriers seem to have crumbled and disappeared as the user base widens dramatically. Other than simple statistics relating to e-mail usage, chatrooms and blog subscriptions, we know surprisingly little about the rapid changes taking place. This book assembles leading researchers on non-verbal communication, emotion, cognition and computer science to summarize what we know about the processes relevant to face-to-face communication as it pertains to telecommunication, including video-conferencing. The authors take stock of what has been learned regarding how people communicate, in person or over distance, and set the foundations for solid research helping to understand the issues, implications and possibilities that lie ahead"--Provided by publisher.
10. 5. 9. 4. 6. Part 2. 3. 7. 2. Part 3. 1. 8. Part 1. Video- and Avatar-Based Communication Facing the future: emotion communication and the presence of others in the age of video-mediated communication Emotions and Visual Cues in HCI Impact of social anxiety on the processing of emotional information in video-mediated interaction Video-linking emotions Virtual gestures: embodiment and non-verbal behavior in computer-mediated communication Emotions in human-computer interaction Nonverbal communication and cultural differences: issues for face-to-face communication over the internet Gendered social interactions in face-to-face and computer-mediated communication To be seen or not to be seen: the presentation of facial information in everyday telecommunications Embodiment and expressive communication on the internet Visual cues in computer-mediated communication: sometimes less is more General Aspects of Visual Cues in CMC Introduction: electronically mediated face-to-face communication: issues, questions, and challenges Elisabeth Oberzaucher, Karl Grammer and Susanne Schmehl. Veikko Surakka and Toni Vanhala Gary Bente and Nicole C. Krämer -- Antony S.R. Manstead, Martin Lea, and Jeannine Goh Pierre Philippot and Céline Douilliez Brian Parkinson and Martin Lea Pio Enrico Ricci Bitti and Pier Luigi Garotti Agneta Fischer -- José-Miguel Fernández-Dols and Pilar Carrera Joseph B. Walther Arvid Kappas and Nicole C. Krämer --
Also able in eBook format.
Keywords: Social networks; Internet -- Social aspects; Teleconferencing